SCIENCE EDUCATION IN THE PHILIPPINE COUNTRYSIDE: A PHENOMENOLOGICAL STUDY - Frank Angelo Pacala (Universitas Muhammadiyah Kuningan, 2023)
The study was designed to explore the science education in the Philippine countryside. Using phenomenological approach and in-depth interview method, the study found out that the science education in poor provinces of the country is weak. There were issues on insufficiency of science infrastructures (e.g., laboratories and internet), out of field teaching, poor reading comprehension, and poor moral of teachers that contribute to the weakening of science education in the countryside. Hence, it is recommended that education managers of the country must solve these issues in order to lessen the burden of teachers and raise the system of science education of the nation.